A Situated Approach to the Understanding of Dynamic Situations. (March 2015) - Chiappe, Dan; Strybel, Thomas Z.; Vu, Kim-Phuong L.
Situation awareness (SA) is an operator's understanding of "what is going on" as he or she manages a complex, dynamic system. In what follows, the case for a situated approach to SA is presented. It claims operators rely on interactions between internal and external representations to maintain their understanding of situations. It is argued that this approach allows researchers to capture two different types of SA—one where operators store SA information directly and one where the information is offloaded but the operator internally represents where to access it from the world and can do so quickly. This position takes a broader unit of analysis on SA than the widely cited Three-Level Model, which claims that only if information is stored internally does it count as SA. We also discuss how to assess SA in situated agents, focusing on the Situation Present Assessment Method (SPAM). We end by discussing some of the potentially fruitful research questions that arise as a result of taking a situated approach as well as implications for interface design.